DECISION TREE DALAM MENGKLASIFIKASI MATA KULIAH TERHADAP PEMAHAMAN SISTEM PEMASARAN - Aslam Fatkhudin (JURNAL ILMU KOMPUTER, 2021)
With the proliferation of applications that support the buying and selling process or better known as e-commerce, and currently online buying and selling is a trend among students, and also a source of income that can be done in spare time, therefore to be able to increase the results of using e-commerce. -commerce required an understanding of the marketing system. In this study, research was conducted on what subjects were taught to students at the Fakultas Teknik dan Ilmu Komputer, Universitas Muhammadiyah Pekajangan Pekalongan which would help in understanding the marketing system. The C4.5 classification algorithm is used to build a decision tree that will make it easier to see courses that can be used to understand the marketing system. After the analysis, the subjects of entrepreneurship, management information systems, design analysis and information systems, data communication and computer networks, computer organization and algorithms and structured programming can be used to gain an understanding of marketing systems.